RESEARCH REVIEW ON THE DESIGN OF FLOW LOSS TEST EQUIPMENT IN PIPE INSTALLATIONS - Fadila, Muhammad Afif; Afrian, Roni; Fitri, Muhamad (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
This literature review study is motivated by the important role of the piping system in determining production results in an industry. The fluid flowing through the piping system experiences instability, resulting in Head Losses. As a result, the fluid pressure is lower than desired, resulting in suboptimal system performance. The aim of this study is to identify a research gap concerning a review of the design of Head Losses test equipment that has been made by previous researchers. The analysis was conducted by literature review using the systematic literature review (SLR) method. Based on a review from 30 journal, it was found that to design a head losses test equipment in a pipe installation, a person must have a basic knowledge of fluid mechanics. Furthermore, an understanding of the function of pumps, pipe installations, pressure gauges, and measuring instruments that are part of the functional system in this test equipment is required. These are the author's references for designing flow loss test equipment that will be used in the Mechanical Engineering Laboratory at Mercu Buana University's Faculty of Engineering.